PREPARATION PROCEDURES OF FUNGAL PHYTO-PATHOGENS SAMPLES FOR ANALYSIS BY MALDI-TOF AND FTIR MICROSCOPY - Erukhimovitch, V.; Tsror Lahkim, L.; Karpasas, M.; Hazanovsky, M.; Huleihil, M.; Huleihel, M. (Journal of Engineering & Processing Management, 2009)
Reliable and rapid identification of phyto-pathogens causing plant diseases is playing an important role in their control strategies. The available methods for identification of fungi are time consuming and not always very specific. MALDI-TOF and Fourier-transform infrared (FTIR) microscopy are proved to be comprehensive and sensitive analytical methods for detection of molecular changes in cells. Due to the similarity between the obtained spectra of different species of fungal pathogens, it is important to choose the most appropriate procedure for the preparation of the examined samples. Such procedure might improve the discrimination between these species. In the present study, we compared between three possible procedures of pathogen sample preparation for their examination by MALDI-TOF and FTIR microscopy. Our results showed that preparation of the fungal sample directly from liquid growth media is considered as the best way of fungal sample preparation for both MALDI-TOF and FTIR microscopy examinations.